ChemInform Abstract: Palladium and Copper Catalyzed Sonogashira Decarboxylative Coupling of Aryl Iodides and Alkynyl Carboxylic Acids. Issue 46 (October 2016) - Maaliki, Carine; Chevalier, Yoan; Thiery, Emilie; Thibonnet, Jerome
Abstract: Efficient microwave promoted reaction conditions are developed for the decarboxylative Sonogashira coupling of propiolic acids with aryl iodides.